Effect of the functionalization of silica nanoparticles as a reinforcing agent on dental composite materials (2015)
ABSTRACT: The present study evaluated the effect of silica nanoparticle aggregation state on the reflectance and crystallinity of dental composite materials. Two types of silica nanoparticles (ca. 10 nm): Aerosil 200 non-funcionalized and Aerosil DT4 funcionalized with 3-methacryloxypropyltrimethoxysilane. Nanoparticles were dispersed in a monomer mix composed by Urethane Dimethacrylate (UDMA) and Ethylene glycol Dimethacrylate (EGDMA) in a 80:20 mass ratio. The particle size of silica and their aggregation state were determined using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), showing that the Aerosil DT4 has dense aggregates with sizes higher than 1 µm; on the other hand the Aerosil 200 showed a particle gel-like structure. The functionalization degree of the Aerosil DT4 was determined by thermogravimetric analysis (TGA), obtaining a value of 7.57% w/w. The composite materials were evaluated by Differencial Scanning Calorimerty (DSC) to determine their crystallinity. The composite material reinforced by Aerosil DT4 showed lower cristallinity than the system with Aerosil 200 due to higher interaction of the polymeric matrix with the funcionalized surface of the Aerosil DT4. The effect of the aggregation state of silica nanoparticles on the optical properties of the composite material was determined by reflectance analysis. The Aerosil 200 sample showed a lower degree of nanoparticle aggregation and higher reflectance than the system with Aerosil DT4. The functionalization of the Aerosil DT4 induced nanoparticle aggregation diminishing the optical properties of the composite material.